(untitled) (Scientific journal of the Fergana State University, 2026)
The article studies the theoretical and methodological foundations of the development of youth economic activity in New Uzbekistan, the deterministic foundations of the development of youth economic activity in New Uzbekistan based on a culture of healthy competition, and the prospects for the development of youth economic activity in New Uzbekistan based on a culture of healthy competition. The deterministic foundations of the development of youth economic activity in New Uzbekistan based on a culture of healthy competition are also analyzed.